2022
DOI: 10.1002/mds.29282
|View full text |Cite
|
Sign up to set email alerts
|

Results of a Randomized Clinical Trial of Speech After Early Neurostimulation in Parkinson's Disease

Abstract: BackgroundThe EARLYSTIM trial demonstrated for Parkinson's disease patients with early motor complications that deep brain stimulation of the subthalamic nucleus (STN‐DBS) and best medical treatment (BMT) was superior to BMT alone.ObjectiveThis prospective, ancillary study on EARLYSTIM compared changes in blinded speech intelligibility assessment between STN‐DBS and BMT over 2 years, and secondary outcomes included non‐speech oral movements (maximum phonation time [MPT], oral diadochokinesis), physician‐ and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…The authors studied patients with an average disease duration of seven years who had recently reported levodopa-induced motor complications. This study confirmed the superiority of early STN-DBS for quality of life and motor improvement and it weighed the potential higher risk of serious adverse events, such as impaired wound healing (3.2 ​%), intracerebral abscess/edema (1.6 ​%), or the need for reoperation (1.6 ​%) [ [115] , [116] , [117] ].…”
Section: Deep Brain Stimulation (Dbs)supporting
confidence: 63%
See 1 more Smart Citation
“…The authors studied patients with an average disease duration of seven years who had recently reported levodopa-induced motor complications. This study confirmed the superiority of early STN-DBS for quality of life and motor improvement and it weighed the potential higher risk of serious adverse events, such as impaired wound healing (3.2 ​%), intracerebral abscess/edema (1.6 ​%), or the need for reoperation (1.6 ​%) [ [115] , [116] , [117] ].…”
Section: Deep Brain Stimulation (Dbs)supporting
confidence: 63%
“…Another prospective study enrolled 30 PD patients without any motor complications and reported that an earlier surgical approach revealed a reasonable safety profile and offered a potential longer period for overall symptom relief [ 117 , 118 ]. Many DBS experts worry that considering DBS after PD diagnosis and before the appearance of motor fluctuations may increase the risk of including patients with atypical parkinsonism or risk overtreating patients who may never develop the degree of disability requiring DBS [ 119 ].…”
Section: Deep Brain Stimulation (Dbs)mentioning
confidence: 99%
“…Moreover, it has been previously reported that speech intelligibility may worsen 1 year after surgery when compared with those under a control group under optimal medical treatment 7 . The majority of the studies regarding the effects of STN-DBS on speech focused on short-term follow-up 7 11 while few studies have assessed the long-term effects 2 , 12 14 . In particular, a previous study reported a worsening of speech intelligibility at five and eight years after surgery in the off-medication condition 12 , while another acoustic study reported variation of the long-term averaged spectrum (LTAS) descriptors for reading and monologue in different stimulation conditions in the long-term after surgery 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, a mechanism for explaining the STN-DBS-related worsening of dysarthria in PD would imply a specific pathophysiological effect of electric stimulation on target neuronal populations. The DBS implanted in the STN may activate antidromically axons of the hyperdirect pathway (i.e., cortico-subthalamic fibers), which in turn may lead to abnormal activation of cortical areas involved in voice production, thus leading to stuttering and spastic speech (16,19,53,(62)(63)(64). Another reasonable mechanism would imply the spread of current from STN to contiguous brain structures owing to horizontal propagation of the electric field and the related volume of tissue activation (VTA) (65).…”
Section: E Ect Of Stn-dbs On Voice In Pd: Putative Mechanismsmentioning
confidence: 99%